Oceanic primary production and marine water quality assesment around chennai coast - Tamilnadu, India - KOTTAIVEDU JAYARAMAN SHARMILA; RAMANATHAN NARAYANAN (International Journal of Pharma and Bio Sciences, 2017)
Pollution of maritime environment is critical throughout the world due to increasing human activity along the coastal boundaries, inputs of pollutants and depletion of maritime resources due to exploitation. Considerable amount of research was entailed on marine pollution; there is an earnest need to quantify the productivity of the oceans, to measure the water quality, nutrients and their resultant effect on littoral habitats. Hence the study is streamlined to appraise the various physico-chemical and biological parameters like Chlorophyll-a, primary productivity at 21 Stations/locations to gauge the current status of water quality and its impact upon marine habitats. The average primary production estimated for the study region (Kovalam to Ennore stretch) is 252.53 g C m2 yr-1. From the sum of primary production, the total yearly fish production for the estuarine, coastal and offshore regions was calculated using empirical relations as 14549.29 tons. However, the fish production data obtained from the fisheries department revealed that there is higher fish catch reported in this region as 35000 tons. This indicates that there is either over exploitation of fisheries or under estimation of primary production rates in the region. From the relationship between primary production and fish production, the average fish catch expected in the study region is estimated as 87.288 ± 47.90 kg/ ha. The fish standing biomass estimated for the study stretch is 0.15 tons /km2 which are comparable with the published values of Sylvie (Guénette Sylvie 2013) for the Bay of Bengal region.